2022
DOI: 10.1186/s13690-022-00864-9
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of excessive gestational weight gain: a systematic review and meta-analysis

Abstract: Background The prevalence of excessive gestational weight gain (EGWG) during pregnancy is increasing, and it is extremely harmful to pregnant women and newborns. Previous studies have suggested that EGWG is associated with various factors. We conducted a systematic review and meta-analysis to identify, quantify and analyze determinants of EGWG and evaluate the effect of these determinants on EGWG. Methods We searched for articles, from January 2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 64 publications
2
22
1
Order By: Relevance
“…In accordance with our results, pregnant women aged above 30 years, and especially above 35 years, showed higher relations with obese conditions. Although, age < 30 years is thought to present more weight gain during pregnancy [ 8 ] other authors describe that women with pregnancy BMI >25 had a higher baseline weight and were more likely to experience excessive gestational weight gain, especially those aged over 30 years [ 17 ]. Additionally, the excess weight of pregnant women led to delivery complications such as abortion, preeclampsia and cesarean births.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with our results, pregnant women aged above 30 years, and especially above 35 years, showed higher relations with obese conditions. Although, age < 30 years is thought to present more weight gain during pregnancy [ 8 ] other authors describe that women with pregnancy BMI >25 had a higher baseline weight and were more likely to experience excessive gestational weight gain, especially those aged over 30 years [ 17 ]. Additionally, the excess weight of pregnant women led to delivery complications such as abortion, preeclampsia and cesarean births.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that weight gain in pregnant women is associated with various factors beyond individual ones. For example, family and social factors are ascribed a potential influence on weight gain [ 8 ]. In this context, ethnicity may have an impact on the lifestyle and dietary habits that lead to increases in the BMI in pre-conceptional women.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Athar et al 6 conducted a scoping review assessing nine articles published between 2015 and 2020 and demonstrated that IPV affects gestational weight gain. Another review conducted by Zhou et al 7 about determinants of excessive gestational weight gain-including 70 studies published between 2009 and 2020, originated in countries from America, Asia, Europe, Oceania and Africademonstrated IPPV as an important risk factor for excessive gestational weight gain. 7 It is worth mentioning that IPPV is also an important national and international public health problem, is defined as "any behavior that inflicts or has the possibility of inflicting physical, psychological or sexual harm to those that are in an intimate relationship".…”
Section: Introductionmentioning
confidence: 99%
“…Another review conducted by Zhou et al 7 about determinants of excessive gestational weight gain-including 70 studies published between 2009 and 2020, originated in countries from America, Asia, Europe, Oceania and Africademonstrated IPPV as an important risk factor for excessive gestational weight gain. 7 It is worth mentioning that IPPV is also an important national and international public health problem, is defined as "any behavior that inflicts or has the possibility of inflicting physical, psychological or sexual harm to those that are in an intimate relationship". 8 Distinct manifestations of violence (psychological, physical or sexual) may coexist within a relationship, in various moments of a couple's life, including pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Body weight before, during, and after pregnancy results from a complex interaction between biological, behavioral, and social factors. Maternal factors related to a higher increase in weight during pregnancy and postpartum are pre-pregnancy body mass index, education, socioeconomic status, age, parity, breastfeeding, food intake, physical activity, sedentarism, sleep hygiene, and psychological stress [12][13][14].…”
Section: Introductionmentioning
confidence: 99%